2014
DOI: 10.1093/intimm/dxu077
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-dioxygenase increases p53 levels in alloreactive human T cells, and both indoleamine 2,3-dioxygenase and p53 suppress glucose uptake, glycolysis and proliferation

Abstract: Indoleamine 2,3-dioxygenase (IDO) suppresses adaptive immunity by inhibiting T-cell proliferation and altering glucose metabolism. The tumor suppressor p53 also alters these cellular processes with similar results. The effect of IDO on p53 and on glucose metabolism was evaluated in alloreactive T cells. Mixed-lymphocyte reactions (MLRs) were performed in the presence or not of the IDO inhibitor, 1-dl-methyl-tryptophan (1-MT) and/or the p53 inhibitor, pifithrin-α (PFT). Cell proliferation, glucose consumption a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 40 publications
8
49
0
Order By: Relevance
“…In the absence of nuclear angiogenin, such as when neamine is used, p53 accumulates and increases the expression of its pro-apoptotic transcriptional targets, including Bax, leading to apoptosis (8). A recent study found that in T-cells isolated from MLRs conducted under the same conditions as the present study, p53 and phosphorylated p53 were robustly expressed (22). In conclusion, the results of the present study show that angiogenin is upregulated during the alloreactive adaptive immune response.…”
Section: Discussionsupporting
confidence: 70%
“…In the absence of nuclear angiogenin, such as when neamine is used, p53 accumulates and increases the expression of its pro-apoptotic transcriptional targets, including Bax, leading to apoptosis (8). A recent study found that in T-cells isolated from MLRs conducted under the same conditions as the present study, p53 and phosphorylated p53 were robustly expressed (22). In conclusion, the results of the present study show that angiogenin is upregulated during the alloreactive adaptive immune response.…”
Section: Discussionsupporting
confidence: 70%
“…In addition to its role in aminoacylation, WARS, like many other tRNA synthethases 41-43 , has been implicated in cellular signaling. A truncated version of WARS is secreted in response to IFNγ and elicits angiostatic effects 23 through inhibition of endothelial cell-cell junctions 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The above findings therefore indicate that IDO1-catalysed LTrp depletion, the synthesis of Kyn pathway metabolites and the activation of AhR and other signalling pathways control the activation status, phenotype and viability of T-cells, B-cells and NK cells in various ways including: (i) induction of cell cycle arrest in T-cells and induction of cell death in T-cells, B-cells and NK cells [51,[229][230][231], (ii) impairment of NK cell-mediated killing by preventing the up-regulation of the activating receptors NKp46 and NKG2D [115], (iii) Th2 polarisation of invariant NKT cells [237], (iv) apoptosis of Th1 cells but not Th2 cells [238], (v) interfering with glucose metabolism in effector T-cells to inhibit proliferation [239,240], (vi) defective TCR activation via the interruption of Ca 2+ signalling [241], (vii) down-regulation of the ζ -chain in the TCR complex on CD8 + T-cells [232], (viii) acquisition and maintenance of an immunosuppressive Foxp3 + Treg (rather than a pro-inflammatory Th17) phenotype by naïve CD4 + T-cells [232,[242][243][244] involving the IDO1-and Kyn/AhRdependent blockade of the down-regulation of the Eos transcription factor (necessary for reprogramming of Tregs into Th17 inflammatory helper-like cells) [245], and (ix) direct activation of the suppressor activity of Foxp3 + Tregs involving the PD-1 (programmed cell death 1)/PD-L (programmed cell death ligand) pathway [226].…”
Section: Lymphocytesmentioning
confidence: 99%